Role of PKC and ERK Signaling in Epidermal Blistering and Desmosome Regulation in Pemphigus - Egu, Desalegn Tadesse; Kugelmann, Daniela; Waschke, Jens (Frontiers in Immunology, 2019)
Desmosomes reinforce cohesion of epithelial cells at the interface between adjacent cells. They include the cadherin-type adhesion molecules desmoglein 1 (Dsg1) and Dsg3. Pemphigus vulgaris (PV) is an autoimmune disease in which circulating autoantibodies (PV-IgG) targeting Dsg1 and 3 cause characteristic epidermal blister formation. It has been shown that PV-IgG binding induced activation of kinases such as extracellular signal-regulated kinases ERK and protein kinase C (PKC), and inhibition of these signaling pathways prevented loss of cell cohesion in cell cultures. However, the role of Erk and PKC) for blister formation and regulation of desmosome ultrastructure in human skin are unknown. Accordingly, we assessed the role of PKC and ERK signaling pathways in blister formation and regulation of desmosome ultrastructure in human epidermis. Here we performed electron microscopy analyses using human skin explants injected with PV-IgG together with inhibitors for PKC or ERK signaling. Inhibition of PKC was not effective to prevent suprabasal blister formation or ultrastructural alterations of desmosomes. In contrast, inhibition of ERK signaling significantly ameliorated blister formation and decrease in the number of desmosomes whereas shortening and splitting of desmosomes and keratin filament insertion were not different from samples treated with PV-IgG alone. However, apical desmosomes between basal and suprabasal cells remained unaltered when ERK signaling was inhibited. Therefore, our results show that inhibition of ERK but not PKC signaling appears to be effective to ameliorate blistering and alterations of desmosome ultrastructure triggered by PV-IgG in human skin.